To Evaluate The Effectiveness of Deep Breathing Exercises on Menopausal Symptoms Among Menopausal Mothers In Selected Community Area, Mangaluru - Mohan, Amitha; D. Almedia, Mrs. Sandhya (International Journal of Scientific Research and Management (IJSRM), 2019)
An Interventional study was conducted to identify the effect of deep breathing exercises on menopausal symptoms among menopausal mothers in community area,Mangalore. Quasi Experimental time series Design was adopted for the present study.A purposive sample of 60 mothers were selected and assigned randomly to Experimental Group and Control Group. The base line data was collected from  the mothers and menopausal symptoms was assessed by using Menopausal Rating Scale.Deep breathing exercises was taught to the mother who belongs to Experimental Group .The menopausal rating scale was assessed for both the control group and Experimental Group.The result revealed that there is a significant reduction in menopausal symptoms in menopausal mothers after performing Deep breathing exercises in the Experimental Group.